A combined vortex lattice lifting line method for unsteady propeller calculations - Büsken, Andreas; Krüger, Stefan (Volume 6: Ocean Engineering, 2021)
This paper presents a Combined Method for the calculation of propeller forces in inhomogeneous inflow. It consists of an extended Goldstein approach based on Lifting Line Theory and a Vortex Lattice Method. After a brief overview of both methods is given, the coupling strategy is described and the additional modifications are explained. A correction factor accounting for the vortex which develops under a separated and later reattached flow on the suction side of the propeller blade is implemented as the first modification. Further, the Lamb-Oseen vortex model is used for the vortices in the free vortex system of the propeller. Finally, some results achieved with the described method are presented and compared to measured values.